The K2-OjOS Project: New and revisited planets and candidates in K2 campaigns 5, 16, & 18. Issue 1 (22nd September 2021) - Castro-González, A; Díez Alonso, E; Menéndez Blanco, J; Livingston, J; de Leon, J P; Lillo-Box, J; Korth, J; Fernández Menéndez, S; Recio, J M; Izquierdo-Ruiz, F; Coya Lozano, A; García de la Cuesta, F; et al.
ABSTRACT: We present the first results of K2-OjOS, a collaborative project between professional and amateur astronomers primarily aimed to detect, characterize, and validate new extrasolar planets. For this work, 10 amateur astronomers looked for planetary signals by visually inspecting the 20 427 light curves of K2 campaign 18 (C18). They found 42 planet candidates, of which 18 are new detections and 24 had been detected in the overlapping C5 by previous works. We used archival photometric and spectroscopic observations, as well as new high-spatial resolution images in order to carry out a complete analysis of the candidates found, including a homogeneous characterization of the host stars, transit modelling, search for transit timing variations and statistical validation. As a result, we report four new planets (K2-355 b, K2-356 b, K2-357 b, and K2-358 b) and 14 planet candidates. Besides, we refine the transit ephemeris of the previously published planets and candidates by modelling C5, C16 (when available) and C18 photometric data jointly, largely improving the period and mid-transit time precision. Regarding individual systems, we highlight the new planet K2-356 b and candidate EPIC 211537087.02 being near a 2:1 period commensurability, the detection of significant TTVs in the bright star K2-184 ( V = 10.35), the location of K2-103 b inside the habitable zone according to optimistic models, the detection of a new single transit in the known system K2-274, and the disposition reassignment of K2-120 b, which we consider as a planet candidate as the origin of the signal cannot be ascertained.